Work Motivation and Quality of Work Life: Its Impact on Organizational Citizenship Behavior of Regional Government Office Employees of North Minahasa Regency - Bertha Ireni Mundung (International Journal of Applied Business and International Management, 2021)
The purpose of this study is to determine whether: (1) work motivation has an effect on OCB; (2) the quality of work life affects OCB; (3) work motivation have an effect on the quality of work life. This study used a quantitative approach with a survey method and multiple linear regression used for technique data analysis. The object of research is the local government office employees of North Minahasa Regency. The sample of employees is taken from the Regional Government Office of North Minahasa Regency, while the data collection used a questionnaire instrument. The result of the study showed that work motivation has a direct effect on OCB amount of 6.98%, the quality of work life has a direct effect on OCB amount of 5.95% and work motivation has a direct effect on the quality of work life amount of 2.43%. The results of this study confirmed that OCB can be improved through work motivation and quality of work life.